Application of FMECA and Fuzzy TOPSIS Methods for Occupational Safety and Health Risk Analysis in the Production Process of Steel Fabrication - Melanida Agustin; Tranggono Tranggono; Mega Cattleya Prameswari A.I. (Universitas KH. Abdul Chalim Mojokerto, 2025)
Every activity in the steel fabrication workshop has potential risks that can cause losses. During 19 months, PT SW recorded 48 workplace accidents. This study aims to identify, evaluate, and analyze occupational safety and health risks, as well as determine alternative solutions to mitigate these risks. Based on the identification results, 88 risks were identified in the steel fabrication workshop. The FMECA method found five main risks: exposure to metal particles, exposure as fast cutting, exposure to sparks, exposure to cutting rays, and noise exposure. Conducted risk cause analysis through fishbone diagrams, resulting in several alternative solutions. The solutions were then prioritized using the fuzzy-TOPSIS method to determine the most effective solution.